Comprehensive Physiology 2023
DOI: 10.1002/cphy.c210037
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Cardiovascular Control in Health and Disease

Abstract: Autonomic neural control of the cardiovascular system is formed of complex and dynamic processes able to adjust rapidly to mitigate perturbations in hemodynamics and maintain homeostasis. Alterations in autonomic control feature in the development or progression of a multitude of diseases with wide-ranging physiological implications given the neural system's responsibility for controlling inotropy, chronotropy, lusitropy, and dromotropy. Imbalances in sympathetic and parasympathetic neural control are also imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 147 publications
0
3
0
Order By: Relevance
“…10 This can be explained by the brain-bridge reflex, according to which the increased preload on the left tilt causes atrial mechanoreceptors to stretch, which increases the heart rate. 18,19 In the present study phenylephrine was used to treat hypotension more frequently in patients with supine position as compared to left tilt position of operating table. In the study conducted by Mendonca et al there was no significant difference in the ephedrine dose required by the mothers in the tilt and the supine group.…”
Section: Discussionmentioning
confidence: 89%
“…10 This can be explained by the brain-bridge reflex, according to which the increased preload on the left tilt causes atrial mechanoreceptors to stretch, which increases the heart rate. 18,19 In the present study phenylephrine was used to treat hypotension more frequently in patients with supine position as compared to left tilt position of operating table. In the study conducted by Mendonca et al there was no significant difference in the ephedrine dose required by the mothers in the tilt and the supine group.…”
Section: Discussionmentioning
confidence: 89%
“…Pathophysiologically, ANS activation, including Sympathetic nervous system (SNS) and renin-angiotensin-aldosterone system (RAAS), serves as determinant within progression and recurrence of cardiovascular diseases ( 39 ). Both animal and clinical studies provide substantial evidence indicating that autonomic imbalance in cardiovascular diseases advances from vagal dominance in the early stages to sympathetic dominance in the later stages ( 40 42 ). The initial surge in sympathetic activity aims to maintain cardiac output.…”
Section: Correlation Between Excessive Sympathetic Nervous System Act...mentioning
confidence: 99%
“…So far, previous studies have shown that the incidence of CVD is closely related to over 300 types of risk factors (33). Among these, environmental factors have a greater impact on CVD, and the relationship between CVD induction and death and environmental climate factors is closely related globally (34).…”
Section: Analysis Of Influencing Factorsmentioning
confidence: 99%